Electrofusion Stimulation Is an Independent Factor of Chromosome Abnormality in Mice Oocytes Reconstructed via Spindle Transfer - Wang, Wei; Shao, Suxia; Chen, Wei; Wang, Weizhou; Chuai, Yunhai; Li, Yunfei; Guo, Yiming; Han, Shujie; Shu, Mingming; Wang, Qihang; Zhang, Lei; Shang, Wei (Frontiers in Endocrinology, 2021)
Oocytes reconstructed by spindle transfer (ST) are prone to chromosome abnormality, which is speculated to be caused by mechanical interference or premature activation, the mechanism is controversial. In this study, C57BL/6N oocytes were used as the model, and electrofusion ST was performed under normal conditions, Ca2+ free, and at room temperature, respectively. The effect of enucleation and electrofusion stimulation on MPF activity, spindle morphology, γ-tubulin localization and chromosome arrangement was compared. We found that electrofusion stimulation could induce premature chromosome separation and abnormal spindle morphology and assembly by decreasing the MPF activity, leading to premature activation, and thus resulting in chromosome abnormality in oocytes reconstructed via ST. Electrofusion stimulation was an independent factor of chromosome abnormality in oocytes reconstructed via ST, and was not related to enucleation, fusion status, temperature, or Ca2+. The electrofusion stimulation number should be minimized, with no more than 2 times being appropriate. As the electrofusion stimulation number increased, several typical abnormalities in chromosome arrangement and spindle assembly occurred. Although blastocyst culture could eliminate embryos with chromosomal abnormalities, it would significantly decrease the number of normal embryos and reduce the availability of embryos. The optimum operating condition for electrofusion ST was the 37C group without Ca2+.